A cost-benefit analysis of the carbon footprint with hydrogen scooters and electric scooters. (10th August 2016) - Chang, Ching-Chih; Wu, Fang-Ling; Lai, Wei-Hsiang; Lai, Ming-Pin
Abstract: This study analyzes the carbon footprint of an internal combustion engine scooter (ICE) and there are four types of electric scooters studied, namely: a hydrogen fueled scooter with on-board methanol steam reforming (on-board SMR), hydrogen scooter with methane steam reforming (SMR), plug-in electric scooter (PEV), and hybrid scooter. This paper also uses a sensitivity analysis to examine how the variations in fuel prices influence the cost-benefit of using a hydrogen scooter. The research results are as follows: (1) SMR and on-board SMR have the smallest carbon (0.0115 kg CO 2, e & 0.0117 kg CO 2, e ), PEV (0.0189 kg CO 2, e ), hybrid scooter (0.0614 kg CO 2, e ) and ICE (0.1378 kg CO 2, e ); the percentage of carbon emissions relative to ICE by each scooter are, in ascending order, 8%, 8%, 14% and 45%; (2) according to the ISO14067 standard, capital goods (fixed costs) cannot be accounted into total life cycle costs, and total life cycle costs excluding fixed costs are in descending order, SMR ($6632), ICE ($4233), on-board SMR ($3643), hybrid scooter ($3368) and PEV ($2824); (3) the variation of fuel price is the key factor of using hydrogen scooters. Highlights: This paper uses the ISO/TS14067: 2013 standard to develop model to examine the carbon footprint of a public transportation. The carbon footprint of the service life cycle (load factor 100%) of a SMR bus is 0.0115 kg CO 2, e . SMR has the smallest carbon footprint (0.0115 kg CO 2, e ). The fuel price is the key factor of using hydrogen scooters.